THE PERSONNEL ADMINISTRATION ACCORDING TO THE FOUR IDDHIPĀDA PRINCIPLES AT KANCHANAPHISEK UDONTHANI TECHNICAL COLLEGE, NONG PHAI SUBDISTRICT, MUEANGUDON THANI DISTRICT, UDON THANI PROVINCE - Inturat, Punnarat; Kangpheng , Samrit; Saengnont, Kasem (Journal of Buddhist Education and Research (JBER), 2024)
The objectives of this research were to study the state and propose guidelines for personnel administration according to the Four Iddhipāda Principles at Kanchanaphisek Udonthani Technical College, Nong Phai Subdistrict, Mueang Udon Thani District, Udon Thani Province. This research employed a mixed-methods approach. The sample group consisted of 113 individuals, including administrators, civil servants, government employees, special instructors, office staff, janitors, and housekeepers. The research tools were a questionnaire and an interview, analyzed using frequency, percentage, mean, standard deviation, and content analysis. The research results were as follows: 1. Personnel administration according to the Four Iddhipāda Principles at Kanchanaphisek Udonthani Technical College, Nong Phai Subdistrict, Mueang Udon Thani District, Udon Thani Province, was generally at the highest level. Among the individual aspects, the aspect with the highest level of practice was management according to Viriya (Effort), followed by management according to Citta (Concentration), then management according to Chanda (Interest). The aspect with the lowest level of practice was management according to Vīmaṁsā (Investigation). 2. The guidelines for personnel administration according to the Four Iddhipāda Principles at Kanchanaphisek Udonthani Technical College, Nong Phai Subdistrict, Mueang Udon Thani District, Udon Thani Province, are as follows: (1) Chanda (Interest): distinguish the importance of tasks, manage work with an appropriate level of importance, and prioritize work steps. (2) Viriya (Effort): plan, inspect, monitor results, and collaboratively find solutions, considering the benefits to be gained. (3) Citta (Concentration): record assigned tasks, outline the scope of work, order tasks according to the plan, track progress, and pay attention to detail throughout the process. (4) Vīmaṁsā (Investigation): uphold correctness, explain reasons to those carrying out tasks, and ensure the assignments are logical and beneficial to both personnel and the organization.